Legal and Ethical Implications of Blockchain Use in Business Transactions - Joel Fredly Pakpahan; Roida Nababan; Samuel Situmorang (Journal of Legal and Cultural Analytics, 2025)
Blockchain technology has brought significant transformations across various industrial sectors due to its transparent, secure, and efficient characteristics. However, its decentralized, transparent, and immutable nature poses legal challenges, particularly concerning personal data protection and ethical use. In Indonesia, the Personal Data Protection Law (UU PDP) and the Electronic Information and Transactions Law (UU ITE) serve as the primary legal frameworks regulating personal data protection. One major issue is the potential conflict between the permanent nature of blockchain and the right to data erasure as stipulated in the UU PDP. Additionally, ethical challenges such as privacy violations, unequal access to technology, and environmental impacts are critical issues that need to be addressed. Dispute resolution in blockchain transactions also faces unique complexities due to blockchain's immutable nature, requiring innovative approaches such as blockchain-based arbitration and smart contract arrangements. Therefore, a specific legal framework and mechanisms are needed to support the safe and responsible development of blockchain while respecting legal principles, ethics, and data protection. Collaboration among governments, businesses, and technology developers is essential to ensure that blockchain can be implemented inclusively and sustainably.